TREATMENT FOR MASTITIS IN SHEEP ON THE BASIS OF RADIO IMPULSE RADIATION - Гарасимчук, І. Д.; Потапський, П. В.; Панцир, Ю. І.; Мазур, В. А. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The paper reports on research into analysis and theoretical justification of applying the informative radio wave electromagnetic fields in treatment for mastitis. Extensive coverage is given to impact of informative parameter of radio wave electromagnetic fields on physical and chemical processes in animal organisms in terms of treatment for mastitis. The interaction model of impulse radio wave radiation of a millimeter range and sheep mammary gland is given. On the basis of a mathematical model and its analysis the range of parameter changes in biotroph of radio impulse electromagnetic fields in mastitis was determined. It has been found that it is necessary to have the membrane potential of at least 110mV that is directed by external source of pulsed electromagnetic radiation of 150 watts to deconstruct the membrane of pathogenic microorganisms in the sheep udder. The author argues that treatment for mastitis should be done with the help of radio impulse radiation of 30-32 GHz pulse-modulated frequency, 80 - 100 s of acquisition time and amplitude of 14 v inside sheep udder